CLINICAL AND LABORATORY CRITERIA USED FOR PATIENT SELECTION FOR ADJUVANT CHEMOTHERAPY IN POST-OPERATIVE BREAST CANCER - Soares, Bianca Pamela; Cardoso, Grasiela Benini dos Santos; Silva, Marcia Fernanda Roque da; Rocha, Roberto Odebrecht (Mastology, 2020)
Introduction: Breast cancer remains the second most common type of cancer in the world and the first among women, with breast cancer incidence rates doubling in the last thirty years. In 2013, the St Gallen Consensus recommended the use of a study of the multigene profile and phenotyping to indicate adjuvance by use of the MammaPrint and Oncotype4 applications; however, as they are not available in the Unified Health System (Sistema Único de Saúde–SUS), clinical predictive criteria and laboratory tests are used for indication of adjuvant therapy. Objective: Evaluation of clinical and laboratory criteria in the selection of patients with breast cancer after surgery for adjuvant chemotherapy and quantification of the factors used in the selected patients and their results. Method: This is a retrospective, cross-sectional observational study with patients over 18 years of age, without gender and race restriction, diagnosed with breast cancer at a public hospital in São Paulo, from 09/10/18 to 10/12/18, who underwent surgical treatment and discussed adjuvant therapy. Patients with metastatic neoplasia and/or undergoing neoadjuvant treatment were excluded. Data collected were: TNM staging, histological type and hormone receptors, age and comorbidities in all medical records collected. Results: 1,390 consultations were carried out, with 42 patients selected, according to the study criteria. Since 40% of the patients were outside the recommended range for breast cancer screening, regarding TNM, late diagnoses were evidenced, with 69% presenting ≥T2 and 36% with lymph node involvement. Of the 42 patients, 98% received adjuvant therapy. Conclusion: It was evidenced by Paik et al., that 92.1% of the 668 patients enrolled in the NSABP B-14 study were considered of intermediate or high risk according to the NCCN and St. Gallen criteria, and by Oncotype DX, 50.6% of the patients were classified as at low risk of recurrence. However, as these are not available in SUS, the present study shows the need to use clinical and laboratory factors to indicate adjuvant therapy, and with these, of the 42 patients, 98% had indication, showing that they are not such effective means in the use of genetic tests, and patients treated by SUS initiate their treatments late, which impacts disease-free survival, since less than 10% of patients received care with early stage neoplasia.